Aswaja Challenge In Globalization Era - Abdul Muid (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2017)
Abstraction: Thinking aswaja is thinking that human life should not only rely on reason but be able to understand and live that the aqli argument should be placed under the Naqli proposition "This thinking is the Thought adopted from Imam Abu Hasan Al-Asy, ari. Therefore, we must fortify ourselves, our families, and our environment, from the thoughts outside Aswaja to strengthen Ahlu Sunnah Wal-Jamah's thinking.